A numerical fire simulation approach for effectiveness analysis of fire safety measures in floating liquefied natural gas facilities. (1st June 2018) - Yang, Ruochen; Khan, Faisal; Yang, Ming; Kong, Depeng; Xu, Changhang
Abstract: Fire remains a serious threat to a floating liquefied natural gas facility. It is of greater concern given the remote locations and limited accessibility of emergency services. This study aims to present a rigorous procedure to study potential accident scenarios in an offshore (floating processing) facility with different ignition source locations and verify the effectiveness of safety measures using computational fluid dynamics code. The uniqueness of the present study is the integration of release, dispersion and fire modeling scenarios, simplifying the fire analysis and increasing its effectiveness from the offshore process system design and analysis perspectives. The first step of the procedure is to identify the range of potential release scenarios and their strength of dispersion in confined and semi-confined spaces. Subsequently, potential fire scenarios are analyzed considering the influence of the location. Computational fluid dynamics models are used to analyze these three steps of the scenarios. Application of the procedure is demonstrated on an offshore facility by analyzing 14 credible scenarios. The ranges of safety measures of these fires are also studied to determine their effectiveness to prevent fires and mitigate their impact. This study provides a simple and efficient way to analyze the impact of key design parameters. In this study, the transition from fire to explosion is not considered and all the environmental factors are assumed to be constants in the simulation. Highlights: A novel rigorous procedure to study potential accident scenarios in an offshore processing facility. Integration of release, dispersion and fire modeling scenarios, simplifying the fire analysis. An effective approach for offshore process system design and analysis considering safety at core theme. Application of the procedure is demonstrated on an offshore production and processing facility.